PENERAPAN METODE PEMBELAJARAN KONSTRUKTIVISME UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI PADA MATERI BENTUK-BENTUK PERMUKAAN BUMI UNTUK SISWA KELAS VII SMP GOTONG ROYONG TOBELO - Darling Surya Alnusra; Andi Suaema (EDUKASI, 2019)
The place of reserach at SMP Gotong Royong, Tobelo. This research aims at knowing the students’ output through the constructivism application and to know improving the output after doing the learning process  using construtivism. The method  used in this reserach was qualitative in the shape of Classroom Action Research (CAR) and using two cycles. Each cycle consisted of planning, doing, and reflection. Based on the result of research, in the cycle 1, the average of the students’ output is 62.08. This value has not get the minimum score or the criterium of minimum completness. In the cycle II, the average of the students’ output is 71.25, this means the students has got minimum score of achievement. The above result shows that the conducted research in cycle I to cycle II get significant improvement.Keywords: constructivism learning, output, KKM